2016
DOI: 10.1128/msystems.00014-16
|View full text |Cite
|
Sign up to set email alerts
|

OsdR of Streptomyces coelicolor and the Dormancy Regulator DevR of Mycobacterium tuberculosis Control Overlapping Regulons

Abstract: Dormancy is a state of growth cessation that allows bacteria to escape the host defense system and antibiotic challenge. Understanding the mechanisms that control dormancy is of key importance for the treatment of latent infections, such as those from Mycobacterium tuberculosis. In mycobacteria, dormancy is controlled by the response regulator DevR, which responds to conditions of hypoxia. Here, we show that OsdR of Streptomyces coelicolor recognizes the same regulatory element and controls a regulon that cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 93 publications
1
34
0
1
Order By: Relevance
“…Despite also being active in mycelium under hypoxic and anoxic conditions, Nar2 is not completely reliant on the bcc‐aa 3 ‐supercomplex for activity (Falke et al ., ). A further difference between the two systems is that hypoxia also induces transcription of the narG2H2J2I2 operon and this is completely dependent on the OsdKR two‐component system ( o xygen, s tress and d evelopment) in mycelium: OsdK is a membrane‐associated histidine kinase and OsdR a predicted DNA‐binding response regulator (Urem et al ., ; Fischer et al ., ). The presumptive osdRK operon is located in the neighbourhood of the nar2 operon in S. coelicolor (Fischer et al ., ) and the regulon controlled by OsdKR is extensive and includes a number of genes and operons encoding stress‐related as well as dormancy proteins (Urem et al ., ).…”
Section: Nitrate Respiration At the Hypoxic‐anoxic Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…Despite also being active in mycelium under hypoxic and anoxic conditions, Nar2 is not completely reliant on the bcc‐aa 3 ‐supercomplex for activity (Falke et al ., ). A further difference between the two systems is that hypoxia also induces transcription of the narG2H2J2I2 operon and this is completely dependent on the OsdKR two‐component system ( o xygen, s tress and d evelopment) in mycelium: OsdK is a membrane‐associated histidine kinase and OsdR a predicted DNA‐binding response regulator (Urem et al ., ; Fischer et al ., ). The presumptive osdRK operon is located in the neighbourhood of the nar2 operon in S. coelicolor (Fischer et al ., ) and the regulon controlled by OsdKR is extensive and includes a number of genes and operons encoding stress‐related as well as dormancy proteins (Urem et al ., ).…”
Section: Nitrate Respiration At the Hypoxic‐anoxic Interfacementioning
confidence: 99%
“…A further difference between the two systems is that hypoxia also induces transcription of the narG2H2J2I2 operon and this is completely dependent on the OsdKR two‐component system ( o xygen, s tress and d evelopment) in mycelium: OsdK is a membrane‐associated histidine kinase and OsdR a predicted DNA‐binding response regulator (Urem et al ., ; Fischer et al ., ). The presumptive osdRK operon is located in the neighbourhood of the nar2 operon in S. coelicolor (Fischer et al ., ) and the regulon controlled by OsdKR is extensive and includes a number of genes and operons encoding stress‐related as well as dormancy proteins (Urem et al ., ). Amongst these is the gene encoding the Nar2‐specific nitrate: nitrite antiporter NarK2, without which nitrate cannot be delivered to the cytoplasmically oriented active site of Nar2, nor can the toxic product of the reaction, nitrite, be exported from the mycelium (Fischer et al ., ).…”
Section: Nitrate Respiration At the Hypoxic‐anoxic Interfacementioning
confidence: 99%
“…Other 499 stress-related proteins being overrepresented in the population of large pellets include 500 polypeptides encoded by genes in the osdR locus, including the gene for the universal stress 501 protein (USP) (SCO0200) (van Veluw et al, 2012). Recent studies revealed that osdR controls 502 development and oxidative stress, and is functionally similar to DosR, the oxygen-sensitive 503 dormancy response regulator in Mycobacterium tuberculosis (Urem et al, 2016). It is 504 interesting to mention that the classes of genes being differently expressed in Streptomyces 505 pellets are known to be subject to transcriptional noise in other microbes (see above).…”
Section: Multilevel Heterogeneity In Liquid Environments 420 421mentioning
confidence: 99%
“…It is known that SCO0200 is under the control of the OsdR/OsdS two component system in S. coelicolor, the functional orthologue of the DevR/DevS of Mycobacterium tuberculosis which controls the dormancy response for surviving the host defence mechanism. The OsdR/OsdS system in Streptomyces has evolved a different role in controlling stress and developmental genes to coordinate the onset of morphological development and antibiotic production in response to environmental conditions 33 . Cluster 3 includes four ATP transporter ATP-binding proteins (AAA+ATPases) also involved in defense mechanisms: SCO3089, SCO3111, SCO3956 and SCO3958.…”
Section: Extensive Changes In 'Translation Efficiency' Occur During Hmentioning
confidence: 99%
“…These include a batch of 'universal stress response' proteins and ABC transporters and, notably, 14 of these translationally-induced genes are contained within a 50-gene segment of the 'redox stress response' cluster (SCO0162-SCO0212) close to one end of the chromosome 33,34 . These gene products are considered to play a critical role in stress adaptation because the genes are induced only at the level of translation, avoiding the requirement for additional transcription; this regulatory strategy ensures a near instantaneous response to the environmental stressor.…”
Section: Extensive Changes In 'Translation Efficiency' Occur During Hmentioning
confidence: 99%